2022
DOI: 10.1111/dar.13449
|View full text |Cite
|
Sign up to set email alerts
|

High cardiovascular risk in older patients with opioid use disorder: Differences with the general population

Abstract: Introduction Cardiovascular disease is a health concern in ageing population with opioid use disorders (OUD). The study aims to analyse the cardiovascular risk factors in individuals with OUD. Methods An observational study was carried out to compare cardiovascular risk factors of adults >50 years with OUD on methadone therapy from public outpatient drug treatment centres, with that of an age‐ and gender‐matched sample (ratio of 1:5) of subjects from a sample of the Spanish population (REGICOR cohort). High ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Similarly, in addition to having a higher BMI, the HTN group was characterized as having negative urine results for all tested substances. Vallecillo et al 7 showed a lower HRN rate as well as a lower BMI among the MMT group members, suggesting an association between these 2 variables, namely, that if BMI is lower than BP is lower, and vice versa. While substance usage was not reported in that study, we assume that it is associated with behavior incompatible with weight gain, which prevents HTN.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, in addition to having a higher BMI, the HTN group was characterized as having negative urine results for all tested substances. Vallecillo et al 7 showed a lower HRN rate as well as a lower BMI among the MMT group members, suggesting an association between these 2 variables, namely, that if BMI is lower than BP is lower, and vice versa. While substance usage was not reported in that study, we assume that it is associated with behavior incompatible with weight gain, which prevents HTN.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in addition to having a higher BMI, the HTN group was characterized as having negative urine results for all tested substances. Vallecillo et al 7 evaluated cardiovascular risk factors among elderly (≥50 years) patients in MMT in comparison to an age-matched general population in Spain. Although those authors found several risk factors among the MMT group members, their results showed a lower HRN rate as well as a lower BMI among the MMT group members, suggesting an association between these 2 variables, namely, that if BMI is lower than BP is lower, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent registry study from Scotland found a high co-presence of respiratory and cardiovascular disease from autopsies for opioid-specific drug-related deaths (DRD) and the authors concluded that circulatory disease was likely related to the quadrupling of methadone-specific DRD in the age group 45 and older [[52]]. Another recent study found older OMT patients to have high cardiovascular risks compared to a gender- and age-matched sample from general populations [[53]].…”
Section: Discussionmentioning
confidence: 99%